Social network analysis on the information exchange of Sorsogon City's CDRRMC during Typhoon Nina - Buenaobra, Nissi Abigail J.; Austria, Aries P.; Calucin, Hannah Trisha M.; Capacia, Gianna C.; Dela Paz, Joel L., Jr. (2019)
The local government units (LGUs) act as frontline agencies in disaster response. To ensure the welfare of their constituents, they perform necessary emergency measures before, during, and after disasters. Crucial to the LGUs’ role is an effective information exchange network with other government agencies, private entities, and nongovernment organizations. Information exchange during disaster response has been a recurring
challenge for authorities as the variables are complex, the environment is unpredictable, and the information demanded and supplied varies. By using social network analysis (SNA), this study explored the information exchange in the interorganizational network of key actors during the disaster response for Typhoon Nina (Nock-Ten) in Sorsogon City, Philippines in
2016. By generating a visual map of the network, SNA enabled the authors to identify the possible information exchange failures, central suppliers and consumers of information, vehicles of information, and macro-level assessment of its effectiveness. This article strengthens the proposition that the actors in the communication network are all essential in the prompt delivery of services during the typhoon. The evident interaction of actors
further established a holistic and substantive information, which helped them make informed decisions for their response efforts.
Keywords: Social network analysis; Emergency management -- Communication systems; Emergency management -- Sorsogon City; Natural disaster warning systems -- Sorsogon; City Disaster Risk Reduction and Management Council (CDRRMC) -- Sorsogon City; Typhoons -- Social aspects